Sweden : Financial Sector Assessment Program Update: Technical Note on Household Indebtedness: Implications for Financial Stability. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2011)
As in other advanced economies, there has been a significant run-up of household debt in Sweden during the last two decades accompanied by rising housing prices, prompting concerns about sustainability and the implications for financial stability. The rise in household debt and the banking system's increased exposure to mortgage debt resulted with the changes in the macroeconomic environment. The note explores implications for financial stability of household indebtedness as well as Sweden's specific institutional features to ensure resilience of the financial system.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet